Mapping waqf research: A 15-year bibliometric study of Malaysia and Indonesia - Misbah, Hanim; Johari, Fuadah (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – This study conducted a comprehensive bibliometric analysis of waqf research from 2010 to 2024, focusing on publications from Malaysia and Indonesia. Methodology – Utilizing the Scopus database, the analysis covers 648 docu-ments sourced from 262 journals, books, and other publications, highlight¬ing the substantial academic interest in waqf. This study identifies key trends, influential authors, and thematic developments in waqf research. Findings – The results show an annual growth rate of 12.61% in waqf publi-cations, with a diverse range of topics, including governance, sustain¬ability, and the integration of waqf with modern financial instruments. Malaysia and Indonesia have emerged as leaders in waqf research, contributing significantly to global discourse. The analysis underscores the collaborative and international nature of waqf research and its integration within broader socioeconomic frameworks. Implications – This bibliometric study provides valuable insights into the evolution of waqf research, informing future studies and policy developments to enhance the socioeconomic impact of waqf initiatives.Originality – This study provides a unique comparative bibliometric analy¬sis of waqf research from Malaysia and Indonesia between 2010 and 2024. The originality lies in the detailed comparison of how these two countries contribute to the global waqf discourse. The analysis highlights both simi¬larities and differences in research focus, showing how each country's unique socioeconomic context shapes its waqf studies, thereby enriching the overall understanding of waqf within broader socioeconomic frameworks.